Emerging Trends in Biomaterials for Tissue Engineering and Regenerative Medicine (International Journal of Scientific Trends, 2023)
This paper provides a comprehensive analysis of the emerging trends in biomaterials for tissue engineering and regenerative medicine. The aim is to explore the advancements in biomaterials research, their applications, and their potential impact on the field. Key topics covered include scaffold design, bioactive materials, smart biomaterials, and 3D bioprinting. The article concludes with a discussion on the challenges and future prospects in this rapidly evolving field.